Gracefully Thriving at 83-3/4 + (A LIFE IN BALANCE AND PURPOSE) (Homoeopathy for All, 2025)
The World Homoeopathy Day is  always a very special occasion for  us when we homoeopaths not only  celebrate the Birth Anniversary  of Dr. Samuel Hahnemann, the  visionary whose legacy has shaped  our identity and profession. It  is a day of connection, offering  us the opportunity to reunite  with fellow homoeopaths, share  cherished memories, and engage  in meaningful conversations.  The event also features ongoing  scientific sessions across various  halls, fostering learning, exchange  of ideas, and advancement in the  field of homoeopathy However, 10th April, 2025, was  very special day for me, as we  had gathered at Mahatma Mandir,  Gandhi Nagar, Gujarat to celebrate  this important day. Amidst our  usual conversations, I was gently  coaxed by Dr. Chaturbhuj Nayak,  former Director Central Council for  Research in Homoeopathy, to write  an article on how I manage to remain  joyful, and healthy even at my age of  83-1/2 and a half.
Keywords: Homoeopathy; occasion; homoeopaths; opportunity